Legal Regulation and Health Risks: Analyzing “Tukang Gigi” in The Context of Service Accessibility - Alfarizi, Mohammad Hanaan; Prasasti, Annisa Widya; Genovés, Manuel Beltrán (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Access to dental services is a challenge for lower to middle-income individuals. Tukang gigi, an alternative to dentists, offers more affordable oral health care. Governed by Ministry of Health Regulation No. 39 of 2014, tukang gigi's authority is limited to acrylic dentures. However, evidence shows unauthorized practices, posing health risks like misdiagnosis and complications. This not only jeopardizes patient health but also undermines the credibility of the dental health profession, eroding public trust.Purposes of the Research: The aim of the research is to find out the legality of dental practices that exceed their authority with a policy approach to the community's need for cheap access to healthMethods of the Research: The research employs a literature study method, specifically normative legal research, focusing on legal norms in laws and regulations. Following a systematic process of collecting, reading, recording, and analyzing library data, the study adopts a doctrinal legal research approach. The emphasis is on elaborating and explaining collected data related to the main research topics.Results of the Research: The current law limits tukang gigi to making and installing detachable dentures that meet health standards. However, tukang gigi often put braces, remove tartar, and color braces outside their allowed scope. Therefore, tukang gigi are not accountable for their activities, leaving consumers or service users vulnerable to malpractice. Despite benefiting from dental artisan work, consumers are ignorant of legal protections when these practitioners breach government rules. Tukang gigi often break the law owing to a lack of information or compliance, so they are at risk without legal protection. In contrast to Spain, where denturists cannot practice dentistry. Only dentists and dental technicians are legally recognized in Spain. This is because dentistry skill requires strict requirements. Dental professionals monitor actions closely to reduce misconduct. Dental care is affordable.